Are ant supercolonies crucibles of a new major transition in evolution?. (27th June 2014) - Kennedy, P.; Uller, T.; Helanterä, H.
Abstract The biological hierarchy of genes, cells, organisms and societies is a fundamental reality in the living world. This hierarchy of entities did not arise ex nihilo at the origin of life, but rather has been serially generated by a succession of critical events known as 'evolutionary transitions in individuality' (ETIs). Given the sequential nature of ETIs, it is natural to look for candidates to form the next hierarchical tier. We analyse claims that these candidates are found among 'supercolonies', ant populations in which discrete nests cooperate as part of a wider collective, in ways redolent of cells in a multicellular organism. Examining earlier empirical work and new data within the recently proposed 'Darwinian space' framework, we offer a novel analysis of the evolutionary status of supercolonies and show how certain key conditions might be satisfied in any future process transforming these collaborative networks into true Darwinian individuals.